The need for patient-centric medicine design: investigating key physical characteristics of oral solid medications to improve acceptance of older patients in Addis Ababa, Ethiopia - Mohammed Chane Assefa; Getahun Paulos; Fikadu Ejeta; Dereje Kebebe Borga (PLoS ONE, 2026)
Patient-centric medicine design emphasizes developing medication products tailored to patients’ specific needs and preferences, including size, shape, color, texture, packaging, and labeling. However, despite increasing recognition of patient-centered pharmaceutical design, evidence remains scarce on how medication and patient characteristics influence medication acceptance among older patients, particularly in low-resource settings such as Ethiopia. This study aimed to identify factors associated with the acceptance of oral solid medications among older adults. An institutional-based cross-sectional study was conducted from May to July 2024 in five public hospitals in Addis Ababa, Ethiopia. Data were collected through an interviewer-administered questionnaire capturing patient-related information (socio-demographics, clinical conditions, and medication beliefs) and medication-related characteristics (size, shape, score line, packaging, texture, dosage form, and labeling). Medication-level acceptance was measured using the MAQ-2019 tool. Descriptive statistics summarized the data, and bivariable and multivariable logistic regression analyses identified predictors of acceptance. Within-patient clustering was accounted for using cluster-robust standard errors. Among 408 older patients and 1,256 oral solid medications, 75% of medications were accepted. Medications sized 6–9 mm were more likely to be accepted (AOR = 6.50, 95% CI: 3.84–10.99, p < 0.001), while those ≥18 mm were less likely to be accepted (AOR = 0.15, 95% CI: 0.06–0.35, p < 0.001) compared with ≤6 mm. Medications with a score line were twice as likely to be accepted (AOR = 1.99, 95% CI: 1.32–3.00, p = 0.001). Older patients preferred small to medium-sized, coated, and scored tablets. Findings underscore the importance of age-appropriate formulation design and patient involvement in medication development.